The Effect of the Synthetic Steroid ORG OD14 on Fibrinolysis and Blood Lipids in Postmenopausal Women - Walker, Isobel D; Davidson, J F; Richards, A; Yates, R; McEwan, H P (Thrombosis and Haemostasis, 1985)
Two groups of postmenopausal women were compared. One group of 13 was given the synthetic steroid Org OD14 to suppress climacteric symptoms and one group of 14 was given placebo. After a 2 week baseline period the subjects received daily for 12 weeks, either 2.5 mg Org OD14 or placebo. There were no significant differences between the groups pre-treatment. Compared with the placebo group, during treatment, the Org OD14 group showed the following significant differences: higher haemoglobin, haematocrit, platelet count, plasminogen, fibrinolytic activity on fibrin plates and antithrombin III and lower fibrinogen. No significant differences between the groups were found in α2 antiplasmin levels, total cholesterol, total triglycerides, bilirubin or transaminase levels but the Org OD14 group had significantly lower levels of HDL cholesterol. With the exception of the haemoglobin and haematocrit levels all of the differences had disappeared by 2 weeks post treatment.
Keywords: Synthetic steroid; Anabolic steroid effect; Fibrinolysis; Blood lipids; Antithrombin III; Plasminogen; Fibrinogen